Taxonomy of Factors Causing Integration Failure during Global Software Development - Atique Ahmad Zafar (IEEE Access, 2018)
Controlling integration failure is one of the major challenges in global software development (GSD) that remains hidden during the development phase and surfaces during the system integration. The integration failures occur as a result of incompatibilities and integration complexities that subsequently lead to delays, extra cost, affect the overall quality, and can even throw the entire GSD project into chaos. A very good understanding of integration failures may help to overcome the integration challenges. The objective of this paper is to explore comprehensively the integration failure factors. This paper thoroughly reviews the available literature. Moreover, the authors have conducted an industrial survey to more closely explore the integration failure factors. This paper largely contributes by devising a detailed taxonomy of 40 integration failure factors. The classification allows to better understand the relationships between the various factors and helps in creating a holistic solution to deal with integration problems in the context of GSD.